A Comparative Study of the Length Patterns of Anterior Cruciate Ligament Reconstructions in the Dog and Man - Palmisano, M. P.; Andrish, J. T.; Olmstead, M. L.; Kambic, Helen; Shah, A. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
To measure the change of length patterns of nine different simulated anterior cruciate ligament (ACL) reconstructions in the canine and human knee.Six fresh-frozen canine cadaver knees and six fresh-frozen human cadaver knees were used in this study. All of the soft tissues were removed from each cadaver knee, leaving the menisci, collateral ligaments and cruciate ligaments intact. After fixation of the femur to a custom-made frame, the ACL was excised. Three tunnels were made each at the ACL origin and insertion, making possible nine reconstruction combinations. A modified intra-articular technique was used to measure change of length, in mm, of each ACL reconstruction through a range of motion of 0 degrees (full extension) to 135 degrees of flexion. A rankorder list of reconstruction combinations was determined. The most isometric combination was determined for the canine and human knees, and trends in length patterns were also evaluated in both species relative to femoral and tibial position. Statistical significance was determined by ANOVA.A combination joining a point caudal to the ACL origin (over-the-top) and anterior on the tibial insertion was found to be the most isometric combination in both the canine and human. The trends in change of length patterns across all reconstruction combinations were similar in the dog and man. Isometry was improved as the reconstruction was placed further posterior on the femur and anterior on the tibia. Conclusions: The canine knee is an appropriate animal model for the study of isometry of the human ACL and its reconstructions.The length patterns of nine simulated Anterior Cruciate Ligament (ACL) reconstructions were determined in the dog and man. In both species, the most isometric reconstruction was one joining points corresponding to a position at the posterior edge of the intercondylar roof of the femur (over-thetop) with a position anterior on the ACL insertion. For the sake of clarity the term anterior cruciate ligament has been used, throughout, for both species, instead of the cranial cruciate ligament (CCL) in the dog. Also knee has been used in place of stifle for the dog.
Keywords: ACL; isometry; canine; human; biomechanics